STRATEGI MANAJEMEN PRODUKSI FILM TELEVISI STARVISION TERHADAP ANGGARAN BIAYA PRODUKSI TERKAIT BUDAYA INDONESIA - Yessy Arisanti Wienata; Citra Ratna Amelia (Jurnal Nomosleca, 2020)
Production management strategiesFTV Starvision related to Indonesian culture are the object of problems in research. The purpose of this study is to provide an understanding that the FTV Starvision shows are highly related to Indonesian culture. The results of the study concluded that Starvision in production FTV used several strategies at each stage of its production. Start from the stage preproduction, production, post production and evaluation. The strategy includes using newcomer performers whose salaries are still low, using locations that are often used so that in terms of licensing it is easier, to use vendors for equipment, and others. These strategies to save production costs. Another strategy is to use location, dialogue, accent, costume, property, which is very thick with Indonesian culture, it to introduce Indonesian culture through television media especially FTV. Key Words : Management Strategy, Film Production Stage, Film Television (FTV) Starvision, Production Cost Budget, Indonesian Culture.DOI: https://doi.org/10.26905/nomosleca.v6i1.3957